Dakwah Dengan Pendekatan Spiritual - Sya’diyah, Halimah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aims to describe how the implementation of H.Nurul Kawakib in the practice of surgery against patients by using a spiritual approach as a holistic process. The implementation of spiritual propaganda is a propaganda media for medical personnel to help someone given to others, which will affect the lives of patients who experience illness or who want to do surgery. This research is a descriptive qualitative research using interpersonal communication analysis study and transactional analysis conducted at H. Nurul Kawakib Lamongan Hospital. In this study, researchers took H. Nurul Kawakib and patients as research subjects, in the process of data collection techniques researchers conducted several stages including: interviews, observation and documentation. From the research results obtained by researchers shows that in the implementation of H. Nurul Kawakib's preaching in the Practice of Operation Against Patients with Spiritual Approach as a Holistic Process Therapy is the implementation of the preaching of a doctor who always invites everyone to always apply the principle of faith in Allah Almighty (hablumminannans) at all times , both when healthy and sick. And also hablumminannas (the attitude of the behavior of a surgeon who has a noble character).